Complement C5a potentiates uric acid crystal‐induced IL‐1β production. Issue 12 (28th October 2014) - An, Ling‐Ling; Mehta, Payal; Xu, Linda; Turman, Sean; Reimer, Thornik; Naiman, Brian; Connor, Jane; Sanjuan, Miguel; Kolbeck, Roland; Fung, Michael
Abstract : Anaphylatoxin C5a released upon complement activation is associated with both acute and chronic inflammations such as gout. The pathogenesis of gout was identified as uric acid crystal deposition in the joints that activates inflammasome, leading to IL‐1β release. However, little is known about the interaction between complement activation and monosodium urate/uric acid (MSU) crystal‐induced inflammasome activation or IL‐1β production. Here, we report that MSU crystal‐induced proinflammatory cytokines/chemokines in human whole blood is predominantly regulated by C5a through its interaction with C5a receptor. C5a induces pro‐IL‐1β and IL‐1β production in human primary monocytes, and potentiates MSU or cholesterol crystals in IL‐1β production. This potentiation is caspase‐1 dependent and requires intracellular Ca 2+ mobilization, K + efflux, and cathepsin B activity. Our results provide insight into the role of C5a as an endogenous priming signal that is required for the initiation of uric acid crystal‐induced IL‐1β production. C5a could potentially be a therapeutic target together with IL‐1β antagonists for the treatment of complement‐dependent and inflammasome‐associated diseases.